Implementasi HMI Pada Penyortiran Buah Jeruk Berbasis PLC - Mardiana, Mardiana; Febriansyah, Aan; Dwisaputra, Indra (Jurnal Inovasi Teknologi Terapan, 2024)
Human Machine Interface (HMI) is a means of liaison and communication media between machines and humans. In this research, HMI was created for citrus fruit sorters that have not yet integrated HMI. This research was carried out to develop a citrus fruit sorter so that it is integrated with HMI. The method used is to implement an HMI on a citrus fruit sorter which is integrated with Arduino, Arduino as a sensor control controller. The orange fruit sorter is installed with a relay which is controlled by an Arduino for input signals to the PLC as the main control which has been programmed using the CX-Programmer. Monitoring and control can be accessed via the HMI display which has been programmed using NB-Designer. The HMI test results were successfully displayed in the form of a graphic visualization containing indicators and ON and OFF buttons for actuators and sensors, as well as displaying data on the number of oranges sorted. The test results carried out by the sorter were able to distinguish green and yellow oranges with an accuracy rate of 93.75% and the implementation of HMI was successful in monitoring and controlling the process of sorting citrus fruit.